Code development for the computational analysis of crack propagation in structures - Antonios Chatzigeorgiou; Efstathios E. Theotokoglou; George I. Tsamasphyros (Fracture and Structural Integrity)
In this study, the main objective was the creation of a code, which gives the capability to a Finite Element Analysis Program with no built-in crack study tools, to study the propagation of a crack, in a cracked surface. For this purpose, the Finite Element Program FEMAP 11.3.2 with solver the NX NASTRAN has been used, and the proposed code was created, using the Application Program Interface (API) of the program. The Linear Elastic Fracture Mechanics (LEFM) theory has been applied to the code, and can predict, if the crack will propagate, the trajectory of the crack, as well as the number of cycle loads required for the propagation of the crack, for given boundary conditions and loads. Finally, the Stress Intensity Factors (SIF) produced by the program, were compared with results from an analytical method. Also, experimental results have been used, for the verification of the results of the trajectory of the propagation, and the cycle loads.